Information and Communication Technologies in the inter-learning - Alejandra Elizabeth García-Suárez; Marcelo Ludgardo Proaño-Cobos; Carlos Fernando Giler-Zúñiga (Maestro y Sociedad, 2018)
The objective of the work is to influence the relationship and influence of Information and Communication Technologies (ICT) on knowledge networks (interlearning), which as a pedagogical-didactic perspective, the teacher can systematize the existence of adaptive and dynamic scenarios, directed to the upward improvement of the quality of the learning of their students. A description is made referring to the conflicts and factors associated to the subject that is approached, for which reason the study has a qualitative approach, based on a scientific and critical dimension, which includes the review of previous investigations referred to this subject, perceived as useful information to formulate and guide educational work.